2021
DOI: 10.1016/j.neo.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

c-Myb interferes with inflammatory IL1α-NF-κB pathway in breast cancer cells

Abstract: Highlights c-Myb attenuates NF-κB activity in breast cancer. Interaction with co-activator p300 is required for NF-κB suppression by c-Myb. c-Myb negatively regulates IL1a transcription in several ER- breast cancer cell lines. Inhibition of IL1α expression mediates the anti-inflammatory effect of c-Myb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…We show that LOX mRNA is upregulated in cells on aged matrices compared to young, and when it is knocked down, E‐CAD in cells on the aged matrix is re‐localized to cell membrane. Remarkably, cytokine levels in the aged microenvironment, especially the uPA/uPAR mediators uPA, [ 59 ] uPAR, SERPINE1, [ 60 , 61 ] ANG, [ 62 ] and OPN, [ 63 , 64 ] as well as the IL1 family [ 65 , 66 ] and IL8, [ 67 ] TGF β family, [ 68 ] MMP2, [ 69 , 70 ] which largely affect cell behavior, including proliferation, migration, and differentiation, as well as cancer progression, [ 71 ] are reduced to the young matrix levels after LOX knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…We show that LOX mRNA is upregulated in cells on aged matrices compared to young, and when it is knocked down, E‐CAD in cells on the aged matrix is re‐localized to cell membrane. Remarkably, cytokine levels in the aged microenvironment, especially the uPA/uPAR mediators uPA, [ 59 ] uPAR, SERPINE1, [ 60 , 61 ] ANG, [ 62 ] and OPN, [ 63 , 64 ] as well as the IL1 family [ 65 , 66 ] and IL8, [ 67 ] TGF β family, [ 68 ] MMP2, [ 69 , 70 ] which largely affect cell behavior, including proliferation, migration, and differentiation, as well as cancer progression, [ 71 ] are reduced to the young matrix levels after LOX knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…144 different SNPs have been described in the IL-1 β gene [52]. At base pairs in these transcription sites, base transitions between C and T have been widely reported [53,54]. Recent studies have shown that IL-1β SNPs rs1143634, rs1143627, rs1143623, and rs10490571 were suggested to be associated with BC risk, while the results of the association of rs16944 with BC risk were inconsistent [55][56][57][58][59][60][61][62].…”
Section: Il-1 Single-nucleotide Polymorphisms and Breast Cancer Riskmentioning
confidence: 99%
“…It was subsequently found that c-Myb reduced autocrine signal transduction of the NF-κB pathway in BC and the ability of BC cells to migrate and cross the endothelial barrier through inhibition of the expression of IL-1α. Overexpression of IL-1α as well as the addition of recombinant protein of IL-1α activated NF-κB signaling and restored the expression of inflammatory signature genes that were suppressed by c-Myb [53]. Mouse models of BC reflect that periodontal inflammation (PI) and the resulting IL-1β promote the expression of CCL5, CXCL12, CCL2, and CXCL5, which in turn recruit MDSCs and macrophages, ultimately creating a premetastatic niche at the site of inflammation [106].…”
mentioning
confidence: 99%
“…IL-1α is a member of IL-1 family and functions as a pro-inflammatory cytokine that promotes the expression of other cytokines, such as IL-6 [ 37 ]. M. Dúcka and colleagues showed that overexpression of IL-1α and the accumulation of its recombinant protein stimulated NF-κB signaling and restored the expression of hallmark inflammatory genes repressed by c-Myb [ 38 ]. HER2 increased drug-resistance-related CSCs in HER2+ breast cancer patients, yet the blocking of IL-1α signaling improved chemotherapy efficacy when combined with cisplatin and paclitaxel.…”
Section: Discussionmentioning
confidence: 99%